Bandwidth Management Design Analysis for Computer Network Infrastructure at SMKN 1 Abdya - Herlina, Elvi (Jurnal Manajemen Informatika Medicom (JMI), 2024)
The need for internet in the learning process has a very significant role so that in its use it is necessary to regulate access and manage bandwidth well for the smooth internet access. This research was conducted to analyze the differences in bandwidth management design for computer network infrastructure in the old design and the new design at SMKN 1 ABDYA. This study aims to see how to analyze the difference in delay and throughput in the bandwidth management design of old and new computer networks. In this study using qualitative research methods where the data obtained by means of observation, interviews and documentation. This research uses the Wireshark version 2.6 application. 6 to see the use of delay and throughput on the bandwidth management design of old and new computer networks. Based on the results of the calculation of the use of delay and throughput using the Wireshark 2.6.6 application, there is a significant difference between the use of delay and throughput in the design of bandwidth management for the old computer network and the design of bandwidth management for the new computer network.